Parameters Design of Power System Stabilizer for Damping Local Mode of Oscillations - Truong, Ngoc Minh; La, Minh Khanh; Nguyen, Hoang Viet (Old Journal, 2017)
The increasing complexity of interconnected power systems due to economy and population development sometimes leads systems to poor dynamic behaviors like power oscillations. These oscillations can cause risks of partial system collapses. Hence, PSSs are used to generate supplementary control signals for the excitation system to damp the low-frequency oscillations. In this paper, the design of PSS for single machine connected to an infinite bus through external line reactance (SMIB) using rotor velocity deviation is proposed. The nonlinear model of a machine is linearized at different operating points. The effectiveness of the proposed method in damping local mode of oscillations, over a wide range of loading conditions and system configurations, is confirmed through phase compensation analysis and simulation results.